Costo efectividad en el diagnóstico y manejo de esguince de tobillo, basados en los criterios de Ottawa durante los años 2014 y 2015 en el Hospital Isidro Ayora - Bustamante Vasquez, Carlos Andres (2018)
Abstract:This study comprised a total of 184 patients, who had a diagnosis of ankle sprain regardless of whether they used the Ottawa criteria. The data obtained were tabulated and plotted in the Microsoft Excel 2013, then compared with other related studies, evidencing that men were the ones with the highest incidence of ankle sprain, constituting 54.3%. The main production mechanism was fall (61.40%). Regarding the applicability of the Ottawa rules, it was only 0.5% (one patient), and the most applied diagnostic method was anteroposterior and lateral ankle radiography performed in 56.5% of patients. The direct cost of the imaging tests (RX) during the two years was $ 2.008.50. Plus the indirect costs evidenced a total of $ 7. 135.55. With which it is concluded that in the Isidro Ayora Hospital, the Ottawa criteria are not applied as a diagnostic tool. Its disuse leads to greater spending in the public system and more time is spent for the diagnosis of ankle sprain.